(Bez)użyteczność badań społecznych. Kilka uwag o socjologii stosowanej = The usability/uselessness of social research. Some observations on applied sociology - Zielińska, Maria (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The main objective of the article is to draw attention to the selected issues for the discussion on the future of sociology in the context of three phenomena: (1) its popularization as a field of study, (2) the implementation of three-cycle sociological studies, in particular first-cycle studies as higher vocational training courses, and (3) potential employment opportunities for sociology graduates on the growing market for social research.
Keywords: socjologia stosowana; badania społeczne